ANALISIS PERLINDUNGAN HUKUM ATAS HAK MORAL PENCIPTA KARYA FOTOGRAFI TERHADAP PENGGUNAAN CIPTAAN FOTOGRAFI OLEH PIHAK LAIN DI MEDIA SOSIAL “INSTAGRAM” SECARA KOMERSIAL BERDASARKAN UNDANG-UNDANG NO.28 TAHUN 2014 TENTANG HAK CIPT - Khusbu Vaswani; Christine S.T. Kansil (Jurnal Hukum Adigama, 2021)
In today's era, technological developments occur very rapidly and it can greatly help economic development by selling products without face to face. Social media can be used for illegal purposes, and can be the best place to do other negative things. This provides an opportunity for everyone who has bad intentions, such as committing fraud, copying works, and even becoming a place for bullying or oppression and spreading hatred to others for the purpose of inciting one another. Online sales are becoming popular in various countries because of the easy and fast way of making, but there are many cases that can occur in the online world that are difficult to get legal protection. Photographic works are very important in the online business world for commercial use of the products sold and these works must be copyrighted to be protected. However, there are many obstacles in online business ventures that occur due to the theft of photographic works of business competitors which are further regulated in Law Number 28 of 2014.